Methodology to support maintenance management for the identification and analysis of the degradation of equipment reliability - Soares, Estefany (2021)
This paper aims to show the development of a methodology to support maintenance management for identification and analysis of equipment reliability degradation to be applied in a manufacturing plant. This methodology includes the application of the Laplace test to identify equipment whose reliability is decreasing since a certain period. An analysis is then carried out to equipment failures in order to identify the critical components and respective failure causes. It ends with identification of improvement proposals for the recurrent failures of the selected components. In the application of this methodology in a manufacturing plant, it was necessary to perform a preparation of the data failure report, based on the Failure Mode and Effects Analysis (FMEA) tool, in order to obtain specific and coherent failure data.